Sistema de indicadores para los procesos financieros de la Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López - Palma Guerrero, Jean Carlos (2022)
The purpose of the curricular integration work was to create a model of a system of indicators for the management of the financial processes of the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López. For which a methodology with a qualitative approach was applied, using inductive, deductive, and analytical methods. Supported by field and bibliographic research. For the collection of information, techniques such as observation, interview and the process sheet were executed, which allowed access to the necessary information. All this helped to carry out the situational diagnosis in the financial department, identifying the processes of deregistration of movable property, in addition to the process of acquisitions of goods and / or services, composed of subprocesses: Modifications and budgetary reprogramming; Negligible amount; Purchase by electronic catalog; Reverse auction; Acquisition of services, consulting; Acquisition of goods, works and/or services under the special regime; Insurance tender; Smaller amount; Inclusive fair; Control of stock goods; Accrued; and Income Record/Payment Request. Noting that one of the factors that affect its correct management is the element of time. Then the key areas of results by performance of the department were identified, these being: human talent, infrastructure, technological equipment and maintenance materials. Finally, the management indicators were defined, focused on the efficiency, effectiveness and effectiveness of the key areas. Subsequently, the technical sheet was designed with which the management of financial processes of the higher education institution was improved, all with the purpose of measuring the existence of failures and optimizing resources.